ANALISIS KEPEMIMPINAN TRANSFORMASIONAL DAN PENGEMBANGAN SUMBERDAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM PROVINSI SULAWESI TENGGARA - La Ode Muhammad Elwan; Bakti Bakti; Taufik Taufik (Universitas Halu Oleo, 2019)
The purpose of the study was to analyze the effect of transformational leadership and human resource development on the performance of employees of the Public Works Office of Southeast Sulawesi Province. The design of this study is associative explanative research. The population of this study was a staff of the Public Works Agency of the Southeast Sulawesi Province. The study sample was selected by cluster random sampling according to the level of education using the Taro Yamane formula. Thus a sample of 88 people. Besides that, 8 informants were used. Data collection using questionnaires, interviews and documentation. Data analysis using multiple linear regression analysis followed by t-test (partial) and F test (simultaneous). The results of the study show that: (1) Transformational leadership has a significant effect on the performance of employees of the Public Works Office of Southeast Sulawesi Province. (2) The development of human resources observed through the dimensions of education and training has a significant effect on the performance of employees of the Public Works Office of Southeast Sulawesi Province. (3) Transformational leadership and human resource development simultaneously have a significant effect on the performance of employees of the Public Works Office of Southeast Sulawesi Province.